Tire wear particles: An emerging threat to soil health. Issue 2 (17th January 2023) - Ding, Jing; Lv, Min; Zhu, Dong; Leifheit, Eva F.; Chen, Qing-Lin; Wang, Yun-Qing; Chen, Ling-Xin; Rillig, Matthias C.; Zhu, Yong-Guan
Abstract: Tire wear particles (TWP) have caused widespread contamination in the environment. However, their behavior and potential impacts in soil remain unclear since studies have so far been mainly conducted in aquatic ecosystems. It is possible that soil ecosystems are already under pressure from pollution by TWP. We here firstly synthesize knowledge about the composition, distribution, and behavior of TWP in soils. By comparing with effects of microplastics (MP) in soil, we further outline several potential impacts of TWP on soil biota and the underpinning mechanisms, and highlight the multiple pathways leading to adverse impacts of TWP on soil microbiota, soil fauna and plants. Furthermore, current knowledge about the effects of TWP is mostly based on single soil microbial species, which may underestimate the effects because of cascading consequences at the community and ecosystem levels. Therefore, more research is urgently needed to clarify the behavior and impacts of TWP from the individual organism to the Earth system level. We suggest that TWP may lead to changes in essential ecosystem services and multifunctionality, and therefore represent an emerging threat to soil health. Graphical abstract: UF0001